Economics of technology adoption: the case of brackishwater aquaculture in Bulacan, Philippines - Padilla, Jose Erezo (1985)
Brackihwater fish ponds are tradition al1y devoted to milk fish culture. However, for the past three to four years , brackishwater milk fish operatorsin Bulacan, Philippine shave been culturing tilapia in addition to their milk fish crops. Owing to the dearth of primary data on this aspect,reasons advanced byre searchers on the emergence of such practice were based on secondary information . The purpose of this study was to provide information on the circumstances surrounding the phenomenon of culturing tilapia in traditional milk fish systems. The under lying reasons for the shifting to tilapia culture were investigated. Another objective was to identify and measure factors which tend to encourage or